Experimental Study on Friction Coefficient and Wear Rate of Gun Metal Sliding Against Different Counterface Materials - Nuruzzaman, D. M.; Chowdhury, M. A.; Roy, B. K.; Sorker, N. Ch.; Karim, R.; Hasan, M.; Mia, S. (Scibulcom Ltd., 2014)
In the present research, friction coefficients of gun metal sliding against different pin materials are investigated and compared. In order to do so, a pin-on-disc apparatus is designed and fabricated. Experiments are carried out when different types of pin such as aluminum, gun metal, copper and brass slide on gun metal disc. Experiments are conducted at normal load 10, 15 and 20 N, sliding velocity 1, 1.5 and 2 m/s and relative humidity 70%. Variations of friction coefficient with the duration of rubbing at different normal load and sliding velocity are investigated. Results show that friction coefficient varies with duration of rubbing, normal load and sliding velocity. In general, friction coefficient increases for a certain duration of rubbing and after that it remains constant for the rest of the experimental time. The obtained results reveal that friction coefficient decreases with the increase in normal load for all the tested pairs. On the other hand, it is also found that friction coefficient increases with the increase in sliding velocity. Moreover, wear rate increases with the increase in normal load and sliding velocity for all sliding pairs. The magnitudes of friction coefficient are different for different material pairs depending on normal load and sliding velocity.